Epidemiology of Gastric Intestinal Metaplasia and Gastric Cancer. Issue 1 (March 2023) - Pham, Codey; Nguyen Wenker, Theresa; El-Serag, Hashem B
Gastric cancer remains one of the most common cancers globally. The pathogenesis of intestinal-type gastric cancer involves pre-malignant stages, including gastric intestinal metaplasia (GIM), the replacement of native gastric foveolar and/or glandular epithelium by intestinal-type epithelium. GIM prevalence is highly variable based on geography and race/ethnicity partly due to the varying prevalence of H. pylori, a potent risk factor. However, gastric cancer incidence does not mirror that of H. pylori, demonstrating a complex interaction between H. pylori and risk factors. We will discuss the epidemiology of GIM and gastric cancer, including incidence trends, risk factors, and implications for future management.